An Unusual Cause of a Pain in the Neck: Pseudoaneurysm from Tuberculous Lymphadenitis - B. Kennedy; D. R. Curran; A. Brady; T. M. O'Connor (Case Reports in Medicine)
A pseudoaneurysm is a haematoma which is surrounded by connective tissue and communicates with the lumen of a ruptured blood vessel. It has no true defined capsule. We describe a case of tuberculous pseudoaneurysm. This is a rare complication of tuberculosis. The clinical presentation of these lesions is highly variable. Definitive diagnosis should consist of contrast-enhanced CT and arteriography. Treatment should include repair of the arterial wall by surgery, endovascular stent-graft insertion, or embolization followed by a full course of antituberculous chemotherapy. Our case is highly unusual in that the pseudoaneurysm arose from the subclavian vasculature in a patient with extrapulmonary tuberculosis only.